Redescription of Tenuipalpus heveae Baker (Acari: Tenuipalpidae) and description of a new species from rubber trees in Brazil - Castro, Elizeu B. [UNESP]; Ramos, Felipe A. M. [UNESP]; Feres, Reinaldo J. F. [UNESP]; Ochoa, Ronald; Bauchan, Gary R. (Les Amis d'Acarologia, 2017)
Tenuipalpus heveae Baker, 1945 was originally described from only female specimens collected on rubber trees from Belterra, State of Pará, Brazil. The original description does not provide enough key information essential for accurate and consistent species identification, and thus, it is difficult to correctly identify this species. In this paper, we redescribe the female, male and immatures of T. heveae, from type and newly collected material, and include additional novel data (e.g. dorsal and ventral ornamentation, leg chaetotaxy and setal measurements) in a standardized form. In addition, we describe Tenuipalpus vieirae n. sp. based on adult females and immatures, collected on Hevea brasiliensis Muell. Arg. and H. guianensis Aubl. (Euphorbiaceae) from Manaus, State of Amazonas, Brazil. We include details of the patterns of ontogenetic setal additions for all stages (except the male of T. vieirae n. sp.) of these two species.
Keywords: Hevea; Ontogeny; Pest mite; Red false spider mite; Sensu lato group; Systematics; Taxonomy; Tenuipalpus vieirae